ANALISIS TITIK RAWAN LONGSOR DAN KECELAKAAN DENGAN MENGGUNAKAN METODE AHP - Ali Akbar Ritonga (Jurnal Informatika, 2018)
This study aims to determine the main points and factors causing landslides and accidents in the Padang-Solok traffic lane. The criteria used are forest damage, rainfall, geology, elevation, slope, soil texture, and road conditions, with data points of 10 points. This study uses the AHP (Analytical Hierarchy Process) method. Based on the results of the study the main factors causing the occurrence of landslides are forest damage with a weight of 0.198, while from the 10 points of the study obtained 80% accuracy of landslides with high, low, medium, and no potential. The highest potential for landslides occurs at point 1 with a weight of 2.98.